2016
DOI: 10.1186/s40104-016-0128-2
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic identification of cryostress in epididymal spermatozoa

Abstract: Background: Cryopreservation of epididymal spermatozoa is important in cases in which it is not possible to collect semen using normal methods, as the sudden death of an animal or a catastrophic injury. However, the freezing and thawing processes cause stress to spermatozoa, including cold shock, osmotic damage, and ice crystal formation, thereby reducing sperm quality. We assessed the motility (%), motion kinematics, capacitation status, and viability of spermatozoa using computer-assisted sperm analysis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 61 publications
3
32
1
Order By: Relevance
“…An ejaculate having less percentage of total motile spermatozoa may fail to reach the site of fertilization due to lack of motility regulating factors secreted in epididymis (Fu-Jun & Xiao-Fang, 2012;Yoon et al, 2016) and proteins such as CatSper, IGF1, and ODF1 (Tamburrino et al, 2014;Cabrillana et al, 2017;Selvaraju et al, 2016b) BSP1 (Somashekar et al, 2015), and TIP39 (Selvaraju et al, 2016a). An ejaculate having less percentage of total motile spermatozoa may fail to reach the site of fertilization due to lack of motility regulating factors secreted in epididymis (Fu-Jun & Xiao-Fang, 2012;Yoon et al, 2016) and proteins such as CatSper, IGF1, and ODF1 (Tamburrino et al, 2014;Cabrillana et al, 2017;Selvaraju et al, 2016b) BSP1 (Somashekar et al, 2015), and TIP39 (Selvaraju et al, 2016a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An ejaculate having less percentage of total motile spermatozoa may fail to reach the site of fertilization due to lack of motility regulating factors secreted in epididymis (Fu-Jun & Xiao-Fang, 2012;Yoon et al, 2016) and proteins such as CatSper, IGF1, and ODF1 (Tamburrino et al, 2014;Cabrillana et al, 2017;Selvaraju et al, 2016b) BSP1 (Somashekar et al, 2015), and TIP39 (Selvaraju et al, 2016a). An ejaculate having less percentage of total motile spermatozoa may fail to reach the site of fertilization due to lack of motility regulating factors secreted in epididymis (Fu-Jun & Xiao-Fang, 2012;Yoon et al, 2016) and proteins such as CatSper, IGF1, and ODF1 (Tamburrino et al, 2014;Cabrillana et al, 2017;Selvaraju et al, 2016b) BSP1 (Somashekar et al, 2015), and TIP39 (Selvaraju et al, 2016a).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, total sperm motility, percentage of type-A sperm, sperm acrosome reaction, sperm fructose uptake, and sperm intracellular calcium signaling were significantly higher in fertile group than the low fertile and infertile groups. An ejaculate having less percentage of total motile spermatozoa may fail to reach the site of fertilization due to lack of motility regulating factors secreted in epididymis (Fu-Jun & Xiao-Fang, 2012;Yoon et al, 2016) and proteins such as CatSper, IGF1, and ODF1 (Tamburrino et al, 2014;Cabrillana et al, 2017;Selvaraju et al, 2016b) BSP1 (Somashekar et al, 2015), and TIP39 (Selvaraju et al, 2016a). The low percentages of acrosomal reacted spermatozoa of low and infertile groups might suggest the inability of spermatozoa to undergo acrosome exocytosis and lack of calcium-mediated signaling cascades further affects penetration of zona pellucida (Tranter et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings, together with the reduced antioxidant activity of SOD and reduced glutathione (GSH) observed in bull and ram sperm after cryopreservation, could explain in part the increased susceptibility of frozen-thawed sperm to suffer lipid peroxidation and oxidative damage [45,46]. Conversely, other studies showed that antioxidant enzymes such as SOD2 and PRDX5 increased after cryopreservation in bull sperm [44,47,48]. Whether this increment is the result of a protein reorganization like in ram sperm, or, on the contrary, if it really reflects a higher activity of these enzymes to protect sperm against oxidative attack, needs to be further verified.…”
Section: Molecular Changes In the Sperm Plasma Membrane During Cryoprmentioning
confidence: 99%
“…In ruminants, two main metabolic pathways, oxidative phosphorylation and glycolysis, produce the energy required to maintain sperm motility in the form of ATP [55]. Comparative proteomics studies between fresh and cryopreserved sperm revealed that freezing-thawing procedures alter the abundance of several enzymes implicated in oxidative phosphorylation and glycolysis in ram, bull and gazelle sperm [38,43,44,47]. Among them, different ATP synthases, COX5B, AK1, NDUFV2, ODPB2, ACO2 and NDPK7 were some of those proteins related to oxidative phosphorylation, while different hexokinases, GPI, ALDOA, GAPDH5, PGK2, PGAM2, PKM2 and TPI were some of those proteins related to glycolysis.…”
Section: Molecular Disturbances In Sperm Energy Metabolism and Motilimentioning
confidence: 99%